Progress in pattern recognition, image analysis, computer vision, and applications : 23rd Iberoamerican Congress, CIARP 2018, Madrid, Spain, November 19-22, 2018, Proceedings /: 23rd Iberoamerican Congress, CIARP 2018, Madrid, Spain, November 19-22, 2018, Proceedings. (2019) - Unknown
No abstract available